Pengaruh Etika Kerja Dan Konflik Kerja Terhadap Kinerja Pegawai Perumda Air Minum Wair Pu’an Kabupaten Sikka - Agnes Evifania; Andreas Rengga; Yustina Olivia Da Silva (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aimed to:(1) find out the a description of employee performance, work ethics, and work conflicts;(2) analyze the influence of work ethics and work conflicts on employee performance either partially or simultaneously. The research population was the employees of Wair Pu'an Regional Water Supply Company of Sikka Regency as many as 50 people. Due to limited population, this study was conducted by census or saturated sampling. Data were collected through questionnaires and analyzed using descriptive methods and inferential statistics i.e. multiple linear regression. Hypothesis testing was done through t-test and F-test. The results of the descriptive analysis showed that the employee performance variable was categorized as good,and work ethics and work conflicts were categorized as very good.The statistical results of the t-test showed that the variables of work ethics and work conflicts had a positive and significant influence on employee performance.The statistical results of the F test indicated that the variables of work ethics and work conflicts had a significant influence on employee performance simultaneously. The result of the determination analysis revealed that the two independent variables in this study were able to explain the fluctuation of employee Performance in Wair Pu’an Regional Water Supply Company of sikka Regency by 36,3%.